Material Recycle Teak Wood Root Waste From The Sea For Home Decoration Products - Hidayah, Alfiyanti Nurril (Corak, 2022)
Recycle material teak wood root waste from the sea is the purpose of this writing; the material that will be used as home decoration products is obtained from fishermen who are at sea and find a lot of teak wood that is washed away then under the edge of the beach then the Recycle process is carried out.  In this design process, it uses a method that includes several stages, including The observation and analysis stage; The imagination stage consists of exploration activities and engineering and material experiments; The imagination development stage is focused on maturing concepts as a result of problem evaluation; The implementation stage of design decisions that are ready to be worked. The method above is then called the process of creating Practice-led Research.